Perencanaan Strategis Si/Ti dengan Metode Analisa Swot dan BSC untuk Meningkatkan Daya Saing di Universitas XYZ - Lestari Retnawati (UIN Sunan Kalijaga Yogyakarta, 2018)
XYZ University is an institution that has applied ICT in academic and non academic operations. ICT infrastructure has been built to connect campus A and campus B with wired and wireless based connectivity to support the running of various information systems as a campus conceptual system. The information system owned by XYZ University has not been fully integrated. There are several systems such as Academic Information System, e-learning, financial system, staffing system, e-Slip and various other applications that are not fully integrated yet. The many systems and applications are an asset to XYZ University's institutions, because in its development it has taken quite a bit of time and resources. Therefore, the institution must fully utilize to support the institution in accelerating the achievement of the vision and mission that has been set so that the application of ICT be aligned with the business interests of the institution of Wijaya Kusuma University Surabaya. Then the institution must prepare a strategic information system / information technology (SI / IT). From here the initial idea of the need for a research entitled